Development of Traditional Game Model 'Etu' to Improve Physical Fitness with Sportsmanship in Elementary School Students in Nagekeo Regency - Timoteus Ajito; Konradus Silvester Jenahut; Osniman Paulina Maure (Journal Of Social Science (JoSS), 2025)
This research aims to develop a physical education teaching model for elementary school students to develop and improve physical fitness with sportsmanship characteristics. This research was carried out because of students' difficulties participating in physical education lessons, and students tend to spend time playing on gadgets and online games. Physical education learning is part of the overall educational process, aiming to improve human performance through physical activity to develop and maintain the body. Based on these problems, researchers are increasingly confident in innovating by developing a traditional game model, 'Etu' (Traditional Boxing), to improve physical fitness with sportsmanship characteristics in elementary school students in Nagekeo district, East Nusa Tenggara. This type of research is Research and Development (R&D), which is used to develop the traditional game model 'Etu' (Traditional Boxing) to improve physical fitness with sportsmanship characteristics. The R&D research used by researchers is the ADDIE development model developed by Dick and Carry. The ADDIE model consists of 5 development stages: analysis, design, development, implementation, and evaluation. Research results from research on developing the traditional Etu (traditional boxing) game model to improve physical fitness characterized by sportsmanship as a learning model equipped with a guidebook. After the physical education learning research products are validated by experts, they are suitable for a physical education lesson. It is a learning model that develops and improves the physical fitness and sportsmanship character of elementary school students.